MASALAH DAN KEBIJAKAN PEMBANGUNAN PERTANIAN DENGAN PENDEKATAN KELEMBAGAAN DI INDONESIA - SBM, Nugroho (JURNAL BISNIS STRATEGI, 2008)
Agriculture Sector has still important roles in Indonesian economy now. These important roles are seen in its share in GDP formation and employment absorption. In agriculture development, Indonesian government is using institutional approach. Institutional approach is being used because conventional approach i.e. NeoÂ Classlcal Approach is failed.Nevertheless, the institutional approach In agriculture development In Indonesia is facing some problems like: subÂcontract system which is not working, moral hazard in agriculture institution like KUO, limited access faced by farmers in input and credit availibility, and good old intitutions destroyed by new institution introduced by the government.So, the right institutional approach need to solve all problem In Indonesian Agriculture development used institutional approach mentioned above.